생강과 법제생강의 DSS(Dextran Sulfate Sodium)로 유도된 마우스의 대장염 억제 효과 - 김신정(Sin-Jeong Kim); 김소희(So-Hee Kim); 임양이(Yaung-Iee Lim); 김용규(Yong-Gyu Kim); 박건영(Kun-Young Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
The purpose of this study was to examine the anti-inflammatory effects of ginger and processed (Beopje) ginger on colitis induced by 2.5% dextran sulfate sodium (DSS) in Balb/c mice. Beopje means a process that herbal medicines are treated by a specific Korean traditional method in order to obtain better pharmacological effects. Mice were fed saline or two different doses of ethanol extracts (ginger and processed (Beopje) ginger) once a day for 14 days. Colitis was induced from day 7 to 14 via administration of 2.5% DSS in drinking water. Experimental animals were divided into four groups: Nor (Normal, 200 ${μ}L$ of saline without 2.5% DSS-treated group), Con (Control, 200 ${μ}L$ of saline and 2.5% DSS treated group), G (500 mg/kg of ginger and 2.5% DSS treated group), and BG (500 mg/kg of Beopje ginger and 2.5% DSS treated group). Body weights of both ginger-administered groups increased compared to the control. Colon length increased to 7.6, and 8.0 cm in the G and BG groups, respectively, whereas that of control was 5.7 cm. Histological colon injury induced by DSS-induced colitis was reduced (P<0.05). In serum and DSS-treated colon tissues, mRNA expression levels of IFN-${γ}$, IL-6, TNF-${α}$, and IL-12 of the Beopje ginger-treated group were significantly suppressed compared to those of the ginger-treated groups. Expression levels of iNOS and COX-2 of the Beopje ginger-treated group were significantly reduced compared to those of the ginger-treated groups (P<0.05), and BG showed stronger anti-inflammatory effects on colitis. These results indicated that ginger exerted anti-inflammatory effects on DSS-induced colitis in mice, and its effects could be increased through Beopje. 본 연구에서는 일반생강과 법제생강의 대장염 염증에 대한 억제 효과와 법제의 가공 처리가 일반생강의 염증 억제 효과보다 우수한 지를 비교하였다. Balb/c 수컷 마우스에 2.5% DSS로 궤양성 대장염을 유도하고, 일반생강과 법제생강 추출물 500 mg/kg을 투여하여 대장염의 염증 억제 효과를 연구하였다. 일반생강과 법제생강은 70% 에탄올로 열수 추출 및 농축하여 실험에 사용하였다. 일반생강과 법제생강 추출물 투여군 모두 대장 길이의 축소와 체중 감소가 대조군보다 유의적으로 억제되었다(P<0.05). 일반생강과 법제생강 추출물 투여군의 대장 길이는 7.6 cm와 8.0 cm로 법제생강 추출물 투여군의 대장 길이가 일반생강 추출물 투여군보다 더 길었다. 대장의 조직학적 관찰에서 대장의 길이의 축소 정도가 증가함에 따라 대장조직 점막층의 선와부의 파괴도 증가되었다. 대장염 염증 초기에 증가하는 염증성 biomarker인 혈청에서의 IFN-${γ}$, IL-6, TNF-${α}$ 및 IL-12의 농도는 일반생강 추출물 투여군보다 법제생강 추출물 투여군에서 유의적으로 더 감소하였고, 대장 조직에서의 이들 사이토카인의 유전자 발현도 같은 경향을 나타내었다(P<0.05). 대장염 조직에서의 염증성 인자인 iNOS, COX-2의 유전자 발현에서도 일반생강군보다 법제생강군의 유전자 발현이 더 유의적으로 감소되었다. 이상의 결과로 DSS로 대장염이 유도된 마우스에서 일반생강과 법제생강의 추출물은 항 염증성 효과를 나타내었고, 법제생강 추출물의 대장염 염증 억제 효과가 일반생강 추출물보다 더 우수하였으며, 이는 법제가공 처리에 의해서 일반생강의 대장염 염증 억제효과가 증가되었다고 사료된다.